Balanced SWOT: Revisiting SWOT Analysis through Failure Management and Success Management - Lee, Junesoo; Lee, Seung Joo; Jung, Kwon (KDI School of Public Policy and Management, 2020)
One of the most popular and widely used frameworks in strategic management is SWOT analysis (or SWOT hereafter), which represents the analysis of “strengths, weaknesses, opportunities, and threats.” SWOT helps identify the positive and negative factors in the external and internal environment of an organization. The primary goal of SWOT is to conduct a situation analysis in order to identify the key issues, problems, or challenges facing the organization and to develop insights into the strategic direction of the organization. SWOT has become widely accepted not only in the business and private sector but also in the public and non-profit sectors, such as the government, schools, hospitals, NGOs, and international organizations. The framework provides a synthesis and logical structure that is clear, objective, comprehensive, and relatively easy to implement. However, the simplicity of SWOT can be a double-edged sword. While praising the convenience of SWOT thanks to its simplicity, SWOT users have also criticized the oversimplified results and processes included in SWOT analyses. In today’s dynamic and rapidly changing environment, the strengths of an organization can become weaknesses, while a threat can become an opportunity.